Routine immunizations during pregnancy, doctors' compliance and patient hesitancy: A two stage study on vaccination uptake. (December 2019) - Psarris, Alexandros; Sindos, Michael; Theodora, Marianna; Antsaklis, Panagiotis; Pergialiotis, Vasilios; Loutradis, Dimitrios; Daskalakis, Georgios
Abstract: Objective: To evaluate the compliance of healthcare professionals with national guidelines and the hesitancy of pregnant women to be immunized against influenza and pertussis. Study design: We conducted a two-stage study. The first stage of our study included all women (n = 197) who gave birth in Alexandra Maternity Hospital in Athens, Greece during a 3-month period (April–June) 2018. They completed a questionnaire regarding their immunization status against influenza and pertussis. If pertinent, they detailed their reasons for not getting immunized. During the second stage of our study, we actively recommended both vaccines to the outpatients of Alexandra Maternity Hospital (n = 195) between September 2018 and January 2019. Results: The majority of women (92.9%) were immunized during childhood according to Greek national immunization guidelines. Almost all the women (98%) stated that they will vaccinate their children. More than half (65.5%) responded that they would have been vaccinated during pregnancy if their doctor had recommended it, but in 73.6% of cases, their doctor did not do so. Only a small proportion of women (16.2%) were immunized against influenza during pregnancy while none of them (0%) received the Tdap vaccine. In most cases (65%), study participants stated they were not immunized because their doctor did not recommend vaccination. Additionally, 9.7% of participants feared possible side effects. During the second stage of our study 94.9% out of 195 women agreed to get vaccinated against influenza and 92.8% against pertussis. Conclusions: It is apparent that the compliance with the immunization guidelines during pregnancy is surprisingly low. However, health professionals appear to be reluctant to recommend vaccination during pregnancy. Women appear to trust their doctors and usually agree with their recommendations.